2005
DOI: 10.1002/jmv.20456
|View full text |Cite
|
Sign up to set email alerts
|

Intragroup antigenic diversity of human respiratory syncytial virus (group A) isolated in Argentina and Chile

Abstract: The intragroup antigenic diversity of the G glycoprotein of 226 human respiratory syncytial virus (HRSV) strains isolated in Buenos Aires (Argentina) and Santiago (Chile) between 1995 and 2002 was evaluated by ELISA with a panel of 14 anti-G monoclonal antibodies (MAbs). Out of 226 strains characterized, 172 (76%) belonged to group A and 54 (24%) to group B. Strains from both groups cocirculated throughout the study period in both countries, except in 1996, 2000, and 2002 when only group A strains were isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
1
18
1
3
Order By: Relevance
“…3 and 5 are globally examined, no obvious correspondence between genotype genetic relatedness and MAb reactivity pattern is observed. These results are generally in agreement with previous reports that detected sporadic antigenic changes in viruses circulating in Argentina and Chile (35,41) or in Germany (36) with the MAbs used in this study but without any distinctive trend.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…3 and 5 are globally examined, no obvious correspondence between genotype genetic relatedness and MAb reactivity pattern is observed. These results are generally in agreement with previous reports that detected sporadic antigenic changes in viruses circulating in Argentina and Chile (35,41) or in Germany (36) with the MAbs used in this study but without any distinctive trend.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, the NA1, NA2, NA4, and ON1 genotypes were regrouped within the GA2 genotype in Table 2. hRSV strains collected through relatively short time periods (15,35,36). Hence, a set of hRSV group A viruses, covering the entire recorded history of this antigenic group and representing all genotypes shown in Table 2 except GA4 and GA6 (for which viruses were not available), was used to reevaluate reactivity with the strain-variable MAbs.…”
Section: Evolution and Dominance Of Group A Genotypes Over Timementioning
confidence: 99%
“…Interestingly, GB13 strains with different predicted G protein lengths were prevalent during these 2 seasons. Previous investigations have reported that a replacement of the predominating HRSV genotype occurs each year (5,11,33). However, we did not identify such an annual shift of the prevailing genotype among hospitalized patients in Belgium.…”
Section: Discussionmentioning
confidence: 99%
“…RSV can be divided into two groups, A and B, using monoclonal antibodies (Mab) directed against gpF and gpG (Cane, 2001). RSV strains have also been further assigned to different antigenic subgroups according to reactivity patterns with Mab panels directed against gpG (Galiano et al, 2005a). The analysis of RSV genes by restriction endonuclease digestion (RFLP) and nucleotide sequencing have demonstrated the occurrence of evolutionary intragroup lineages or genotypes, which have worldwide distribution (Cane and Pringle, 1992;Cane, 2001).…”
Section: Introductionmentioning
confidence: 99%